Physical frailty and fitness of older driver (Colombia Medica, 2017)
Aim: to analyze the association between physical frailty and the results of fitness capacity exams for driving vehicles among elder Brazilians.Methods: this is a cross sectional study, performed in traffic medicine clinics of the city of Curitiba (Brazil). The data was collected through the physical frailty tests, the use of a structured questionnaire, and searches on the records of the Brazilian National Register of Qualified Drivers.To analyze the information, the authors used descriptive statistics and non-parametrical tests.Results: One hundred seventy two elderly people, of whom 56.4% pre-fragile and 43.6% non-fragile. 25.0% were considered fit for driving, 68.6% were considered fit, but with some restrictions, and 6.4% were placed as temporarily unfit for driving. There was no association between frailty condition and the final results for driving fitness (p= 0.8934). Physical frailty was significantly associated to the restrictions observed for those who were fit under restrictions (p= 0.0313), according to the weekly amount of kilometers traveled (p= 0.0222), and to car accidents occurred after the age of 60 (p= 0.0165).Conclusion: Physical frailty was significantly associated to the restrictions related to driving, reason to which makes important to manage frailty over this group of drivers. However, no association observed between physical frailty and the final result for driving vehicles.